Genome analysis and the human X chromosome. - Mandel, J; Monaco, A; Nelson, D; Schlessinger, D; Willard, H (1992)
A unified genetic, physical, and functional map of the human X chromosome is being built through a concerted, international effort. About 40 percent of the 160 million base pairs of the X chromosome DNA have been cloned in overlapping, ordered contigs derived from yeast artificial chromosomes. This rapid progress toward a physical map is accelerating the identification of inherited disease genes, 26 of which are already cloned and more than 50 others regionally localized by linkage analysis. This article summarizes the mapping strategies now used and the impact of genome research on the understanding of X chromosome inactivation and X-linked diseases.